(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article analyzed Tennessee Williams’ Clothes for Summer Hotel – A Ghost Play, framing it as Pop Art dramaturgy. It explored the fragmentation of dialogues, actions, and the post-dramatic approach to time and space. It investigated these expressionist elements that reinforce its antirealistic character, challenging stigmas by portraying Zelda as a character transcending temporal reality, memory, and dream. Williams confronts dramatic narratives, providing an uncomfortable perspective to traditional standards of psychological realism associated with his work, offering an alternative interpretation.